Printing process of low-porosity H13 die steel
Through selective laser melting equipment, the H13 mold steel is printed, and the process parameters and processing flow are optimized, and the problem of poor surface performance of existing mold steel is solved, and the molding of low porosity and low surface roughness is achieved, which meets the high level of industrial molds. Strength and high toughness requirements.
Patent Information
- Application Number
- CN202411554958.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-02-18
AI Technical Summary
In the existing H13 mold steel additive manufacturing process, the porosity and surface roughness are poor, making it difficult to meet the requirements of photovoltaic aluminum profile extrusion molds.
The H13 mold steel is printed using selective laser melting equipment. By optimizing the parameter design of laser power, scanning speed and point spacing, combined with the drying treatment and cross-scan mode of spherical powder, the residual stress and deformation are reduced, and heat treatment and thermal isostatic pressure are used. Treatment improves density.
The low porosity and low surface roughness forming of H13 mold steel is achieved. The product has high strength and high toughness, which is suitable for industrial mold needs under complex working conditions.
Smart Images

Figure CN119457120A_ABST
Abstract
Description
[Technical field]
[0001] The invention relates to the technical field of photovoltaic bracket manufacturing, and in particular to a printing process of low-porosity H13 mold steel. [Background technology]
[0002] In the production and manufacturing of photovoltaic brackets, 6XXX series aluminum alloy is used for extrusion heat treatment to form aluminum profiles, and then the products are formed after sulfuric acid anodizing, cutting and finishing processes. The extrusion process is a crucial link in the production and manufacturing of photovoltaic aluminum profiles. The molds used in the extrusion process are divided into one-out-one and one-out-multiple molds according to the shape of the extruded aluminum profiles. The corresponding molds are called single-hole molds and one-mold multi-hole molds. The extrusion of aluminum profiles is carried out under high temperature and high pressure, so the surface quality of the mold and its material composition cannot be ignored. The impact on the extrusion process.
[0003] The existing H13 steel additive manufacturing method has poor surface performance due to poor control of the metal laser printing process, such as too high porosity and too large surface roughness, which is not suitable for use as an extrusion die for photovoltaic aluminum profiles. However, since additive manufacturing has its advantages, the process must be continuously improved to make the mold steel produced by additive manufacturing suitable for aluminum profile extrusion.
[0004] In view of this, the inventor of this case conducted in-depth research on the above-mentioned issues, which led to the emergence of this case. [Summary of the invention]
[0005] The present invention aims to solve the technical problem of poor surface performance of H13 molds in the prior art, and provides a printing process for low-porosity H13 mold steel.
[0006] The present invention is implemented as follows: a printing process for low-porosity H13 mold steel, during printing, a selective laser melting device is used to print and generate the H13 mold steel, the laser power of the selective laser melting device is controlled at 300W-400W, the scanning speed is controlled at 700mm / s-1200mm / s, and the point pitch of the laser point is controlled at 0.08mm-0.12mm.
[0007] Furthermore, during printing, the laser power of the selective laser melting device is controlled at 350 W, the scanning speed is controlled at 850 mm / s, and the dot pitch is controlled at 0.10 mm.
[0008] Furthermore, before printing: prepare spherical H13 mold steel powder, wherein the particle size of the spherical H13 mold steel powder is 15-53 μm; dry the spherical H13 mold steel powder; during printing: preheat the working platform of the selective laser melting equipment to 150-200°C, evenly spread a layer of spherical H13 mold steel powder on the working platform, and use a cross-scanning mode to scan and melt the powder along a preset path to form a solid layer; after each layer is melted, the working platform will drop a layer thickness, and a layer of powder will be spread again, and the above process will be repeated until a mold billet is formed; after printing: perform heat treatment, hot isostatic pressing treatment, and surface treatment on the mold billet in turn to obtain a H13 mold steel finished product, and then perform porosity detection and surface roughness detection on the H13 mold steel finished product.
[0009] Furthermore, the spherical H13 mold steel powder includes C: 0.40%, Si: 1.00%, Mn: 0.30%, Cr: 5.00%, Mo: 1.40%, V: 0.90%, P≤0.010%, S≤0.010%, and the rest is Fe.
[0010] Furthermore, the thickness of the powder layer is controlled to be between 20 μm and 40 μm.
[0011] Furthermore, the cross scanning mode is to scan alternately at 45° or 90° when each layer is formed.
[0012] Furthermore, during printing, the entire process is carried out in an inert gas environment, wherein the inert gas includes 20% nitrogen and 80% argon, and the oxygen content is controlled below 100 ppm.
[0013] Furthermore, the heat treatment is as follows: the mold steel billet is first heated to 1030° C. for quenching, kept warm for 30 minutes, oil-cooled, and then tempered to 560° C. for 3 times.
[0014] Furthermore, the hot isostatic pressing treatment is to treat the tempered die steel at 100 MPa and 1200° C. for 2 hours.
[0015] The advantages of the present invention are as follows: the printing process of the H13 mold steel of the present invention uses the MT650 equipment produced by AVIC Matt, and optimizes the design of three parameters, namely, laser power, scanning speed, and dot pitch, so that the printed H13 mold steel finished product has the advantages of low porosity and low surface roughness; residual stress and deformation are reduced by heat pretreatment of the working platform and cross scanning; the density of the mold steel billet is further improved by hot isostatic pressing treatment; this printing process realizes the low porosity and low surface roughness forming of H13 mold steel by precisely controlling each link, and the product can meet the high strength and high toughness requirements of industrial molds, ensuring its stable performance under complex working conditions.
Brief Description of the Drawings
[0016] The present invention will be further described below in conjunction with embodiments with reference to the accompanying drawings.
[0017] Figure 1 This is the effect diagram of the H13 die steel finished product of the experimental group 1 of the present invention under the SEM electron microscope.
[0018] Figure 2 This is the effect diagram of the H13 die steel finished product of the experimental group 2 of the present invention under the SEM electron microscope.
[0019] Figure 3 This is the effect picture of the H13 die steel finished product of the experimental group 3 in the present invention under the SEM electron microscope.
[0020] Figure 4 This is a rendering of the H13 die steel product of Experimental Group 4 of the present invention under a SEM electron microscope.
[0021] Figure 5 This is the effect diagram of the H13 die steel finished product of the experimental group 5 of the present invention under the SEM electron microscope.
[0022] Figure 6 This is the effect diagram of the H13 die steel finished product of Experimental Group 6 in the present invention under a SEM electron microscope.
[0023] Figure 7 This is the effect diagram of the H13 die steel finished product of comparison group 1 in the present invention under a SEM electron microscope.
[0024] Figure 8 This is the effect diagram of the H13 die steel finished product of comparison group 2 in the present invention under a SEM electron microscope.
[0025] Fig. 9 This is the effect diagram of the H13 die steel finished product of comparison group 3 in the present invention under a SEM electron microscope.
[0026] Fig.10 This is the effect diagram of the H13 die steel finished product of comparison group 4 in the present invention under a SEM electron microscope. [Specific implementation method]
[0027] In order to better understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with the accompanying drawings and specific implementation methods.
[0028] It should be noted that the terms "center", "longitudinal", "lateral", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", etc., indicate positions or positional relationships based on the positions or positional relationships shown in the drawings, and are only for the convenience of describing these embodiments and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operate in a specific orientation. In addition, the terms "first", "second", etc., etc. are only used for descriptive purposes, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, features defined as "first", "second", etc. may explicitly or implicitly include one or more of the features.
[0029] In order to achieve the surface quality control of H13 mold steel, in addition to the composition control of H13 mold steel, the process setting during additive manufacturing also affects the surface quality of the mold steel. Therefore, the present invention provides a printing process for low-porosity H13 mold steel, and the selective laser melting equipment uses the MT650 equipment produced by AVIC Matt, including the following steps:
[0030] Before printing: first prepare spherical H13 mold steel powder, the particle size of the spherical H13 mold steel powder is 15-53 μm; then dry the spherical H13 mold steel powder, and preheat the working platform of the selective laser melting equipment to 150-200° C. to reduce thermal stress during the forming process and avoid cracking.
[0031] During printing: the laser power of the selective laser melting equipment is controlled at 300W-400W, the scanning speed is controlled at 700mm / s-1200mm / s, and the point distance of the laser point is controlled at 0.08mm-0.12mm; a layer of spherical H13 mold steel powder is evenly spread on the work platform, and the laser uses a cross-scanning mode to scan and melt the powder along the preset path to form a solid layer; after each layer is melted, the work platform will drop a layer thickness, and a layer of powder will be spread again, and the above process will be repeated until the mold billet is formed. The preset path is the shape of each layer of H13 mold steel.
[0032] After printing: the mold steel billet is subjected to heat treatment, hot isostatic pressing treatment, and surface treatment in sequence to obtain the H13 mold steel finished product, and then the porosity and surface roughness tests are performed on the H13 mold steel finished product.
[0033] The H13 mold steel printing process of the present invention optimizes the design of three parameters, namely, laser power, scanning speed and dot pitch, so that the printed H13 mold steel finished product has the advantages of low porosity and low surface roughness; residual stress and deformation are reduced by heat pretreatment of the working platform and cross scanning; the density of the mold steel billet is further improved by hot isostatic pressing treatment; this printing process realizes the low porosity and low surface roughness forming of H13 mold steel by precisely controlling each link, and the product can meet the high strength and high toughness requirements of industrial molds, ensuring its stable performance under complex working conditions.
[0034] Preferably, the spherical H13 mold steel powder is dried at 60° C. for 12 hours to avoid moisture absorption affecting fluidity.
[0035] Preferably, during printing, the laser power of the selective laser melting device is controlled at 350W, the scanning speed is controlled at 850mm / s, and the dot pitch is controlled at 0.10mm. In this step, the dot pitch is the spacing between the laser dots, and the laser power, scanning speed and dot pitch are adjusted in the parameter setting of the MT650 device. Laser scanning is performed according to the set parameters to ensure that the H13 mold steel powder is completely melted and well combined with the work platform. Appropriate laser power ensures that the powder is completely melted, avoids porosity or ablation, and improves density. A centered and uniform scanning speed can control heat accumulation, help improve interlayer bonding strength and improve surface roughness. The dot pitch setting directly affects the density, surface quality and printing efficiency of the H13 mold steel. The optimal dot pitch control improves the interlayer bonding quality and surface finish, and reduces the use of consumables.
[0036] Preferably, the spherical H13 mold steel powder includes C: 0.40%, Si: 1.00%, Mn: 0.30%, Cr: 5.00%, Mo: 1.40%, V: 0.90%, P≤0.010%, S≤0.010%, and the rest is Fe.
[0037] Preferably, the particle size of the spherical H13 mold steel powder is 28-32 μm, and the powder is sieved using a sieve to ensure uniform particle size; the more spherical the powder shape, the better the fluidity, which helps to improve the forming quality.
[0038] Preferably, the spherical H13 mold steel powder has a flat layer thickness of 20 μm-40 μm. Use a powder spreader or a scraper to evenly spread the spherical H13 mold steel powder on the work platform to ensure a uniform powder layer thickness to prevent pores and cracks. Preferably, the spherical H13 mold steel powder has a flat layer thickness of 30 μm.
[0039] Preferably, the cross scanning mode is to scan alternately at 45° when each layer is formed to reduce residual stress.
[0040] Preferably, the entire printing process is carried out in an inert gas environment, wherein the inert gas includes 20% nitrogen and 80% argon, and the oxygen content is controlled below 100 ppm to avoid oxidation of the H13 mold steel during the forming process.
[0041] Preferably, the heat treatment is to heat the mold steel billet to 1030°C for quenching, keep it warm for 30 minutes, oil cool it, and then temper it to 560°C for 3 times. Tempering after quenching can improve the hardness and toughness of the mold steel billet while maintaining a balance between hardness and toughness.
[0042] Preferably, the hot isostatic pressing treatment is to treat the tempered die steel at 100 MPa and 1200° C. for 2 hours to further eliminate residual pores and improve the material density of the die steel billet.
[0043] Preferably, the porosity of the H13 mold steel finished product is measured using a porosity meter, and the porosity meter is a Quanta 650FEG porosity meter produced by Thermo Fisher Scientific.
[0044] Preferably, a surface roughness tester is used to measure the surface roughness of the H13 die steel finished product, and the surface roughness tester is a MarSurfXR 20 surface roughness tester produced by Marl, Germany.
[0045] The following is an illustration of the beneficial effects of the printing process using the low-porosity H13 die steel of the present invention through several experimental groups and comparative groups. (The spherical H13 die steel powder of each experimental group and comparative group includes C: 0.40%, Si: 1.00%, Mn: 0.30%, Cr: 5.00%, Mo: 1.40%, V: 0.90%, P≤0.010%, S≤0.010%, and the rest is Fe.)
[0046] Experimental Group 1
[0047] Spherical H13 mold steel powder is prepared, and the particle size of the spherical H13 mold steel powder is 28-32μm; the spherical H13 mold steel powder is dried, and the working platform of the selective laser melting device is preheated to 150-200℃. The H13 mold steel is printed using a selective laser melting device, and the laser power of the selective laser melting device is controlled at 300W, the scanning speed is controlled at 700mm / s, and the point distance of the laser point is controlled at 0.1mm; the spherical H13 mold steel powder is evenly spread on the working platform, and the spherical H13 mold steel powder has a layer thickness of 30μm. The laser uses a cross scanning mode to scan and melt the powder along a preset path to form a solid layer; after each layer is melted, the working platform will drop a layer thickness, and a layer of powder will be spread again, and the above process will be repeated until the mold billet is formed. The mold billet is heat treated, hot isostatic pressed, and surface treated in sequence to obtain a finished H13 mold steel product, and then the porosity and surface roughness of the finished H13 mold steel product are tested.
[0048] Experimental Group 2
[0049] Prepare spherical H13 mold steel powder, the particle size of the spherical H13 mold steel powder is 28-32μm; dry the spherical H13 mold steel powder, and preheat the working platform of the selective laser melting equipment to 150-200℃. Use the selective laser melting equipment to print and generate H13 mold steel, the laser power of the selective laser melting equipment is controlled at 350W, the scanning speed is controlled at 850mm / s, and the point distance of the laser point is controlled at 0.1mm; evenly spread a layer of spherical H13 mold steel powder on the working platform, the spherical H13 mold steel powder has a layer thickness of 30μm, and the laser uses a cross scanning mode to scan and melt the powder along a preset path to form a solid layer; after each layer is melted, the working platform will drop a layer thickness, and a layer of powder will be spread again, and the above process will be repeated until the mold billet is formed. The mold billet is heat treated, hot isostatic pressed, and surface treated in sequence to obtain the H13 mold steel finished product, and then the porosity and surface roughness of the H13 mold steel finished product are tested.
[0050] Experimental Group 3
[0051] Spherical H13 mold steel powder is prepared, and the particle size of the spherical H13 mold steel powder is 28-32μm; the spherical H13 mold steel powder is dried, and the working platform of the selective laser melting equipment is preheated to 150-200℃. The H13 mold steel is printed using a selective laser melting equipment, and the laser power of the selective laser melting equipment is controlled at 400W, the scanning speed is controlled at 1200mm / s, and the point distance of the laser point is controlled at 0.1mm; the spherical H13 mold steel powder is evenly spread on the working platform, and the spherical H13 mold steel powder has a layer thickness of 30μm. The laser uses a cross scanning mode to scan and melt the powder along a preset path to form a solid layer; after each layer is melted, the working platform will drop a layer thickness, and a layer of powder will be spread again, and the above process will be repeated until the mold billet is formed. The mold billet is heat treated, hot isostatic pressed, and surface treated in sequence to obtain a finished H13 mold steel product, and then the porosity and surface roughness of the finished H13 mold steel product are tested.
[0052] Experimental Group 4
[0053] Spherical H13 mold steel powder is prepared, and the particle size of the spherical H13 mold steel powder is 28-32μm; the spherical H13 mold steel powder is dried, and the working platform of the selective laser melting equipment is preheated to 150-200℃. The H13 mold steel is printed using a selective laser melting equipment, and the laser power of the selective laser melting equipment is controlled at 350W, the scanning speed is controlled at 850mm / s, and the point distance of the laser point is controlled at 0.08mm; the spherical H13 mold steel powder is evenly spread on the working platform, and the spherical H13 mold steel powder has a layer thickness of 30μm. The laser uses a cross scanning mode to scan and melt the powder along a preset path to form a solid layer; after each layer is melted, the working platform will drop a layer thickness, and a layer of powder will be spread again, and the above process will be repeated until the mold billet is formed. The mold billet is heat treated, hot isostatic pressed, and surface treated in sequence to obtain a finished H13 mold steel product, and then the porosity and surface roughness of the finished H13 mold steel product are tested.
[0054] Experimental Group 5
[0055] Spherical H13 mold steel powder is prepared, and the particle size of the spherical H13 mold steel powder is 28-32μm; the spherical H13 mold steel powder is dried, and the working platform of the selective laser melting equipment is preheated to 150-200℃. The H13 mold steel is printed using a selective laser melting equipment, and the laser power of the selective laser melting equipment is controlled at 350W, the scanning speed is controlled at 850mm / s, and the point distance of the laser point is controlled at 0.12mm; the spherical H13 mold steel powder is evenly spread on the working platform, and the spherical H13 mold steel powder has a layer thickness of 30μm. The laser uses a cross scanning mode to scan and melt the powder along a preset path to form a solid layer; after each layer is melted, the working platform will drop a layer thickness, and a layer of powder will be spread again, and the above process will be repeated until the mold billet is formed. The mold billet is heat treated, hot isostatic pressed, and surface treated in sequence to obtain a finished H13 mold steel product, and then the porosity and surface roughness of the finished H13 mold steel product are tested.
[0056] Experimental Group 6
[0057] Prepare spherical H13 mold steel powder, the particle size of which is 28-32 μm; dry the spherical H13 mold steel powder, and preheat the working platform of the selective laser melting device to 150-200°C. Use the selective laser melting device to print and generate H13 mold steel, the laser power of the selective laser melting device is controlled at 380W, the scanning speed is controlled at 1000mm / s, and the point distance of the laser point is controlled at 0.10mm; evenly spread a layer of spherical H13 mold steel powder on the working platform, the spherical H13 mold steel powder has a layer thickness of 30μm, and the laser uses a cross scanning mode to scan and melt the powder along a preset path to form a solid layer; after each layer is melted, the working platform will drop a layer thickness, and a layer of powder will be spread again, and the above process will be repeated until the mold billet is formed. The mold billet is subjected to heat treatment, hot isostatic pressing treatment, and surface treatment in sequence to obtain the H13 mold steel finished product, and then the porosity and surface roughness of the H13 mold steel finished product are tested.
[0058] Comparison group 1
[0059] Spherical H13 mold steel powder is prepared, and the particle size of the spherical H13 mold steel powder is 28-32μm; the spherical H13 mold steel powder is dried, and the working platform of the selective laser melting device is preheated to 150-200℃. The H13 mold steel is printed using a selective laser melting device, and the laser power of the selective laser melting device is controlled at 280W, the scanning speed is controlled at 700mm / s, and the point distance of the laser point is controlled at 0.10mm; the spherical H13 mold steel powder is evenly spread on the working platform, and the spherical H13 mold steel powder has a layer thickness of 30μm. The laser uses a cross scanning mode to scan and melt the powder along a preset path to form a solid layer; after each layer is melted, the working platform will drop a layer thickness, and a layer of powder will be spread again, and the above process will be repeated until the mold billet is formed. The mold billet is heat treated, hot isostatic pressed, and surface treated in sequence to obtain a finished H13 mold steel product, and then the porosity and surface roughness of the finished H13 mold steel product are tested.
[0060] Comparison group 2
[0061] Spherical H13 mold steel powder is prepared, and the particle size of the spherical H13 mold steel powder is 28-32μm; the spherical H13 mold steel powder is dried, and the working platform of the selective laser melting device is preheated to 150-200℃. The H13 mold steel is printed using a selective laser melting device, and the laser power of the selective laser melting device is controlled at 430W, the scanning speed is controlled at 1200mm / s, and the point distance of the laser point is controlled at 0.10mm; the spherical H13 mold steel powder is evenly spread on the working platform, and the spherical H13 mold steel powder has a layer thickness of 30μm. The laser uses a cross scanning mode to scan and melt the powder along a preset path to form a solid layer; after each layer is melted, the working platform will drop a layer thickness, and a layer of powder will be spread again, and the above process will be repeated until the mold billet is formed. The mold billet is heat treated, hot isostatic pressed, and surface treated in sequence to obtain a finished H13 mold steel product, and then the porosity and surface roughness of the finished H13 mold steel product are tested.
[0062] Comparison group 3
[0063] Prepare spherical H13 mold steel powder, the particle size of the spherical H13 mold steel powder is 28-32μm; dry the spherical H13 mold steel powder, and preheat the working platform of the selective laser melting equipment to 150-200℃. Use the selective laser melting equipment to print and generate H13 mold steel, the laser power of the selective laser melting equipment is controlled at 350W, the scanning speed is controlled at 850mm / s, and the point distance of the laser point is controlled at 0.07mm; evenly spread a layer of spherical H13 mold steel powder on the working platform, the spherical H13 mold steel powder has a layer thickness of 30μm, and the laser uses a cross scanning mode to scan and melt the powder along a preset path to form a solid layer; after each layer is melted, the working platform will drop a layer thickness, and a layer of powder will be spread again, and the above process will be repeated until the mold billet is formed. The mold billet is heat treated, hot isostatic pressed, and surface treated in sequence to obtain the H13 mold steel finished product, and then the porosity and surface roughness of the H13 mold steel finished product are tested.
[0064] Comparison group 4
[0065] Spherical H13 mold steel powder is prepared, and the particle size of the spherical H13 mold steel powder is 28-32μm; the spherical H13 mold steel powder is dried, and the working platform of the selective laser melting equipment is preheated to 150-200℃. The H13 mold steel is printed using a selective laser melting equipment, and the laser power of the selective laser melting equipment is controlled at 350W, the scanning speed is controlled at 850mm / s, and the point distance of the laser point is controlled at 0.13mm; the spherical H13 mold steel powder is evenly spread on the working platform, and the spherical H13 mold steel powder has a layer thickness of 30μm. The laser uses a cross scanning mode to scan and melt the powder along a preset path to form a solid layer; after each layer is melted, the working platform will drop a layer thickness, and a layer of powder will be spread again, and the above process will be repeated until the mold billet is formed. The mold billet is heat treated, hot isostatic pressed, and surface treated in sequence to obtain a finished H13 mold steel product, and then the porosity and surface roughness of the finished H13 mold steel product are tested.
[0066] Table 1 Relevant parameters of H13 die steel products obtained in experimental groups 1-7
[0067]
[0068] According to the data in Table 1:
[0069] 1. The die steel of experimental group 2 has the lowest porosity and surface roughness.
[0070] 2. According to experimental groups 1-3, 6, and comparative groups 1 and 2, it can be seen that when the point distance is 0.10mm, since the laser power and scanning speed have a corresponding linear relationship when set, the increase of laser power helps to completely melt the powder and improve the density and strength; but too high power may cause over-melting and ablation of the mold, forming a rough surface or holes, and even causing deformation and cracking; reducing the laser power may lead to insufficient melting of the material, increase the porosity, and reduce the mechanical properties and density of the mold. Therefore, it is best to control the laser power at 350W.
[0071] 3. According to experimental groups 1-3, 6, and comparative groups 1 and 2, it can be seen that: increasing the scanning speed improves the printing efficiency, but it is easy to cause incomplete melting, resulting in pores in the material, reducing density and strength; reducing the scanning speed helps to increase the melting depth and interlayer bonding strength, but reducing the printing speed may lead to thermal stress accumulation and increase the risk of deformation. Therefore, the scanning speed is optimally controlled at 850mm / s.
[0072] 4. According to experimental groups 2, 4, 5 and comparative groups 3 and 4, it can be seen that when the laser power is 350W and the scanning speed is 850mm / s, the dot pitch is too large, the porosity becomes higher, the surface is too rough, and it may also lead to poor interlayer bonding; if the dot pitch is too small, it can reduce the porosity and surface roughness, improve the interlayer bonding quality and surface finish, but it will also increase material consumption. Therefore, it is best to control the dot pitch at 0.10mm.
[0073] 5. It can be seen from the experimental test data of experimental groups 1-6 and comparative groups 1-4 that when H13 mold steel is printed and formed, in addition to controlling the composition of the spherical H13 mold steel powder, the process parameter setting during printing also affects the surface quality of the mold steel. The present invention controls the laser power of the selective laser melting equipment to 300W-400W, the scanning speed to 700mm / s-1200mm / s, and the point distance of the laser point to 0.08mm-0.12mm during printing. The printed H13 mold steel finished product has the advantages of low porosity and low surface roughness. The product can meet the high strength and high toughness requirements of industrial molds and ensure its stable performance under complex working conditions.
[0074] Although the specific implementation modes of the present invention are described above, those skilled in the art should understand that the specific implementation modes described are only illustrative and are not intended to limit the scope of the present invention. Any equivalent modifications and changes made by those skilled in the art in accordance with the spirit of the present invention should be included in the scope of protection of the claims of the present invention.
Claims
1. A printing process for low porosity H13 die steel, characterized in that: During printing, a selective laser melting device is used to print and generate H13 mold steel. The laser power of the selective laser melting device is controlled at 300W-400W, the scanning speed is controlled at 700mm / s-1200mm / s, and the point pitch of the laser point is controlled at 0.08mm-0.12mm.
2. The printing process of low porosity H13 mold steel according to claim 1, characterized in that: During printing, the laser power of the selective laser melting device is controlled at 350 W, the scanning speed is controlled at 850 mm / s, and the dot pitch is controlled at 0.10 mm.
3. The printing process of low porosity H13 mold steel as claimed in claim 2, characterized in that: Before printing: preparing spherical H13 mold steel powder, wherein the particle size of the spherical H13 mold steel powder is 15-53 μm; drying the spherical H13 mold steel powder; During printing: preheat the working platform of the selective laser melting equipment to 150-200℃, evenly spread a layer of spherical H13 mold steel powder on the working platform, and the laser scans and melts the powder along the preset path in a cross-scanning mode to form a solid layer; after each layer is melted, the working platform will drop a layer thickness and spread a layer of powder again, and repeat the above process until the mold billet is formed; After printing: the mold steel billet is subjected to heat treatment, hot isostatic pressing treatment, and surface treatment in sequence to obtain the H13 mold steel finished product, and then the porosity test and surface roughness test are performed on the H13 mold steel finished product.
4. The printing process of low porosity H13 mold steel as claimed in claim 3, characterized in that: The spherical H13 die steel powder comprises C: 0.40%, Si: 1.00%, Mn: 0.30%, Cr: 5.00%, Mo: 1.40%, V: 0.90%, P≤0.010%, S≤0.010%, and the rest is Fe.
5. The printing process of low porosity H13 mold steel as claimed in claim 3, characterized in that: The thickness of the powder layer is controlled at 20 μm-40 μm.
6. The printing process of low porosity H13 mold steel as claimed in claim 3, characterized in that: The cross scanning mode is to scan alternately at 45° or 90° when each layer is formed.
7. The printing process of low porosity H13 die steel as claimed in claim 3, characterized in that: During printing, the entire process is carried out in an inert gas environment, wherein the inert gas includes 20% nitrogen and 80% argon, and the oxygen content is controlled below 100 ppm.
8. The printing process of low porosity H13 mold steel as claimed in claim 3, characterized in that: The heat treatment is as follows: the mold steel billet is first heated to 1030° C. and quenched, kept warm for 30 minutes and then oil-cooled, and then tempered to 560° C. and tempered three times.
9. The printing process of low porosity H13 die steel as claimed in claim 3, characterized in that: The hot isostatic pressing treatment is performed on the tempered die steel under the conditions of 100 MPa and 1200° C. for 2 hours.